EL ESCÁNER CONVENCIONAL, UNA HERRAMIENTA ÚTIL PARA LA CATALOGACIÓN DE ORGANISMOS MARINOS (Boletín de Investigaciones Marinas y Costeras, 2016)
The Flat Bed Scaner, a helpfull tool for marine organisms cataloguing.A cheap and versatile methodology  to get digital images of dry and wet preserved organisms, using a flat bed scanner, is presented. To obtain the images of  wet specimens, a shallow  pool was glued on top of the scanner glass. The pool is filled with water or alcohol and the organisms are immersed and their structures expanded. The best images were obtained with organisms between 1.5 and 15 cm in length. The depth of field was limited to 1.2 cm. These images are also useful for taxonomical research without the need of manipulating the organisms;  they can be used too, to compare with better accuracy certain structures between different specimens.